Antineoplastic Effects of Honokiol on Melanoma. (17th January 2017) - Guillermo-Lagae, Ruth; Santha, Sreevidya; Thomas, Milton; Zoelle, Emily; Stevens, Jonathan; Kaushik, Radhey S.; Dwivedi, Chandradhar
Abstract : Honokiol, a plant lignan has been shown to have antineoplastic effects against nonmelanoma skin cancer developments in mice. In this study, antineoplastic effects of honokiol were investigated in malignant melanoma models. In vitro effects of honokiol treatment on SKMEL-2 and UACC-62 melanoma cells were evaluated by measuring the cell viability, proliferation, apoptosis, cell cycle analysis, and expressions of various proteins associated with cell cycle progression and apoptosis. For the in vivo study, male nude mice inoculated with SKMEL-2 or UACC-62 cells received injections of sesame oil or honokiol for two to seven weeks. In vitro honokiol treatment caused significant decrease in cell viability, proliferation, cell cycle arrest, increased apoptosis, and modulation of apoptotic and cell cycle regulatory proteins. Honokiol caused an accumulation of cells in the G2/M phase of the cell cycle in SKMEL-2 and G0/G1 phase in UACC-62 cells. An elevated level of caspases and PARP were observed in both cell lines treated with honokiol. A decrease in the expression of various cell cycle regulatory proteins was also observed in honokiol treated cells. Honokiol caused a significant reduction of tumor growth in SKMEL-2 and UACC-62 melanoma xenografts. These findings suggest that honokiol is a good candidate for further studies as a possible treatment for malignant melanoma.